Research on operation control model of FAO system under compound-fault scene in urban rail transit. Issue 2 (20th July 2018) - Hou, Zhongwei; Bao, Feng; Du, Zixue; Yang, Zhen
ABSTRACT: This paper aims at the control decision of the compound-fault scene in urban rail transit Fully Automatic Operating (FAO) system. Under the compound-fault scene of vehicle fire and station fire occurring simultaneously, a bi-level optimization model is proposed for the operation control model of urban rail transit FAO system, and the validity of the model is verified by the simulation experiment. The simulation results show that the decision model can effectively find the optimal control points for the compound-fault occurrence of urban rail transit FAO system out, so as to carry out the active control and improve the operation efficiency of the urban rail transit system.